The Effect of Simulation Methods on Preparedness Flood Disaster - Syam, Ilham; Yulianita, Marisna Eka; Efendi, Suradi; Dewi, Chitra; Zulhijayanti, Zulhijayanti (GLOBAL HEALTH SCIENCE GROUP, 2023)
Throughout 2022, the National Disaster Management Agency (BNPB) noted 3,531 natural disaster events in Indonesia. The disaster that occurred dominated by floods, namely 1,524 incidents Where amount This equivalent to 43.1% of the total national disaster events. The aim of this research is to determine the effect of simulation methods on flood disaster preparedness at SD Inpres Nipa-Nipa Makassar City. This research uses a